Fault-Tolerant Architecture for Real-Time Payment Processing in Large-Scale Telecom Billing Systems - Patel, Parth (International Journal of Emerging Research in Engineering and Technology, 2023)
Payment processing systems that serve large consumer-facing organizations must handle millions of transactions per day while maintaining consistent reliability. A single point of failure in the payment pipeline can result in measurable revenue loss and customer dissatisfaction. This paper presents a fault-tolerant architecture for integrating CyberSource payment services within a large-scale Internet Service Provider (ISP) billing platform that handles payments for over three million active customer accounts. The system achieves high availability through a combination of idempotent API design, exponential backoff retry logic, a circuit breaker mechanism calibrated for payment gateway behavior, asynchronous event queuing using Apache Kafka, and distributed transaction tracing. The architecture reduces mean recovery time from over eighteen minutes to under one minute, eliminates duplicate charge incidents through idempotency enforcement, and sustains 99.94% transaction success rates during observed periods of CyberSource API instability. This paper describes the design decisions behind each component, the CyberSource REST API integration approach, lessons learned from operating this system in production and observed performance data before and after the fault-tolerant design was adopted.